Analysis of Foreign Trade Indices: Complementary Trade Index - Barreno Benavides, Luis (2012)
The Complementary Trade Index shows the correlation between a country's import and export structures. These indices make it possible to determine whether the value of trade between two countries is higher or lower than expected, based on their importance in world trade, in addition to offering an idea of the way in which the flow of foreign trade operates.